Analisis Sentimen Komentar Instagram Terkait Persepsi Hidup Sehat Menggunakan Algoritma BERT-LSTM - Putri, Audiva Tartila Daning (UNIVERSITAS RAHARJA, 2025)
The perception of a healthy lifestyle is crucial for physical and mental well-being, especially with the rising cases of non-communicable diseases in Indonesia. Instagram is an effective platform for education, enabling sentiment analysis of the perception of a healthy lifestyle using comment data from posts on the @ayosehat.kemkes account. This involves data collection and preprocessing, labeling, and splitting the data into training, validation, and testing sets. By combining the BERT-LSTM algorithm to classify sentiment into positive, negative, and neutral, the testing results showed that the best model achieved an accuracy of 89.20%, with a precision of 89.49%, recall of 89.20%, and an F1-score of 88.74%, with an 80:10:10 dataset split ratio.